Unieruchamiająca moc baz danych - Drozdowski , Rafał (Człowiek i Społeczeństwo, 2013)
Digital databases democratizes access to information and start a whole new set of social relations. On the other hand, the gigantism of digital databases disincentive to engage in their replenishment and hinders the use of their resources. This article is an attempt to answer the question of what features of modern databases and the management rules increase the chance of them activating and ties making potential.